Factores profesionales e institucionales relacionados con la calidad del registro de enfermería de los servicios de medicina del Hospital Básico Baba diciembre 2022- abril 2023. - Salinas Rodríguez, Alexander Israel (2023)
The objective of this investigation was to determine the relationship that exists between professional an institutional factor with the quality of nursing records in the medical services of the basic Hospital of Baba during a period of 4 months. The population chosen for the execution of this research was made up of 28 nursing professionals and 100 nursing records established in the medical records during the months of study. The survey was implemented as a specific technique to apply the questionnaire and at the same time the collection of information by means of observation is counted as an instrument. After obtaining the results, it was possible to highlight that institutional factor are the most related to the quality of nursing records compared to professionals. Among the nursing professionals surveyed, it was highlighted that 17.8 % presented high knowledge and regular quality in making the records, while 21.4% have low knowledge and perform good quality in making the nursing records.